Analyzing the Role of Social and Spiritual Capital on Employee Performance in Pesantren - Kamaluddin, Imam; Nurunisa, Dwi Kurnia; Putri, Eka Risana (International Conference on Humanity Education and Society (ICHES), 2024)
Abstract Pesantren as the oldest religious education institution in Indonesia, not only takes part in the field of education but also has a role in improving and empowering the economy through various business units. Several studies mention that pesantren can also influence the economy and empowerment of the surrounding community, contributing to the alleviation of poverty in the community, thanks to the social capital provided by kiaiKiyai and pesantren administrators. However, the wide distribution of pesantren in Indonesia shows that areas with many pesantren have the highest poverty rates. This research focuses on the role of the social and spiritual capital of the pesantren community, especially on employees of pesantren workers, either teachers or other employees. This research uses descriptive qualitative methods and purposive sampling in data collection. The respondents were selected according to the criteria, namely workers or employees in Islamic boarding school. The results of this study indicate that the social capital and spiritual capital of pesantren do not directly affect community empowerment, but employee performance can mediate and influence community empowerment through the performance of employees who work in pesantren. So it is necessary to further study the influence of social and spiritual capital on community empowerment.